Darussalamah Al-Mubarok Islamic Boarding School Strategy Cianjur West Java In Preventing Radicalism Through Asatiyyah Islamic Religious Education - Muntaha, Aa; Arifin, Bunyanul; Abdurrohman, Asep; Mukhtarom, Asrori (Universitas Muhammadiyah Tangerang, 2023)
Wasatiyyah Islamic Religious Education remains an important issue today, especially sincesocial conditions are faced with the challenges of increasingly open radicalism movements.Wasatiyyah Islamic Religious Education can be used as an anti-radicalism movement. Thisthesis analyzes the problem of wasatiyyah Islamic religious education at the DarussalamahAl-Mubarok Islamic Boarding School, Cianjur, West Java. There are three questions posed:First, what are the symptoms of Islamic radicalism in Islamic boarding schools? Second,how to prevent Islamic radicalism in Islamic boarding schools? How can the concept ofwasatiyyah Islamic education be used as a solution to prevent radical Islamic education? Inorder to answer the above problems, qualitative data collection was carried out throughobservation, interviews, and documentation at the Darussalamah Al-Mubarok IslamicBoarding School, Cianjur, West Java.There were 10 informants interviewed by the researcher. The results of the study show that:First, in concept and practice the symptoms of radicalism are characterized by anunderstanding of shariah which is the main doctrine in radical Islamic organizations suchas: shariah understanding of the Leadership System ( Daulah/Khilafah ), Application ofIslamic Law ( Tahkim al-Syariah ), War ( Jihad ), Mahdhah Worship, and Loyalty toMuslims and Deliverance from Kafirs ( Al-Wala' wa Al-Bara' ). Second, after experiencingchanges in Islamic boarding schools to prevent with wasatiyyah Islamic education. Third,practically wasatiyyah Islamic education has succeeded in changing the understanding andactions of pesantren elements (clerics, ustadz, santri, and other administrators). Due to thissocio-religious change, Darussalamah Al-Mubarok Islamic Boarding School hopes: to re-adapt to the wasatiyyah Islamic education environment or adapt the community environmentto the needs of the pesantren; to position the aim of the pesantren as a regulator ofcommunity relations with other diverse social systems; and to maintain the identity of thepesantren as a wasatiyyah Islamic institution.Keywords: Pesantren, Islamic Radicalism, Wasatiyyah Islamic Education.